Optimizing Production for Maximum Profit in Kripik Ma'Nung MSMEs Using CPLEX-Based Linear Programming - Rahma, Nafia Rahma; Dwi Agustina Kurniawati; Noor Saif Muhammad Mussafi (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2025)
Micro, Small, and Medium Enterprises (MSMEs) significantly contribute to the economic development of Indonesia. However, many MSMEs still rely on intuition and past experience rather than data-driven decision-making, resulting in suboptimal profit outcomes. This study aims to determine the optimal production combination to maximize profit in Kripik Ma’Nung, a halal-certified MSME that produces five types of traditional chips. A linear programming approach was applied using CPLEX Optimization Studio 22.1.2 to analyze real production data, including unit cost, production time, and selling price. The decision variables were the weekly production quantities of each chip type, subject to constraints on production cost and time. The initial production plan yielded a weekly profit of IDR 370,200 with a production time of 1,478.8 minutes. After optimization, the model suggested producing only 166 units of sale banana chips, which increased the profit to IDR 448,200, reduced production time to 1,377.8 minutes, and cut costs by IDR 78,000. These results demonstrate a 21% improvement in profit efficiency and highlight the effectiveness of linear programming as a decision-support tool. The study encourages broader adoption of optimization techniques among MSMEs to enhance resource utilization and operational decision-making.